Prolonging the delivery of influenza virus vaccine improves the quantity and quality of the induced immune responses in mice - Beukema, Martin; Gong, Shuran; Al-Jaawni, Kasem; de Vries-Idema, Jacqueline J.; Krammer, Florian; Zhou, Fan; Cox, Rebecca Jane; Huckriede, Anke (Frontiers in Immunology, 2023)
Influenza vaccines play a vital role in protecting individuals from influenza virus infection and severe illness. However, current influenza vaccines have suboptimal efficacy, which is further reduced in cases where the vaccine strains do not match the circulating strains. One strategy to enhance the efficacy of influenza vaccines is by extended antigen delivery, thereby mimicking the antigen kinetics of a natural infection. Prolonging antigen availability was shown to quantitatively enhance influenza virus-specific immune responses but how it affects the quality of the induced immune response is unknown. Therefore, the current study aimed to investigate whether prolongation of the delivery of influenza vaccine improves the quality of the induced immune responses over that induced by prime-boost immunization. To study this, mice were given daily doses of whole inactivated influenza virus vaccine for periods of 14, 21, or 28 days; the control group received prime-boost immunization with a 28 days interval. Our data show that the highest levels of cellular and humoral immune responses were induced by 28 days of extended antigen delivery, followed by 21, and 14 days of delivery, and prime-boost immunization. Moreover, prolonging vaccine delivery also improved the quality of the induced antibody response, as indicated by higher level of high avidity antibodies, a balanced IgG subclass profile, and a higher level of cross-reactive antibodies. Overall, our findings contribute to a better understanding of the immune response to influenza vaccination and have important implications for the design and development of future slow-release influenza vaccines.